Exploring the Relationship between Social Support and Parental Stress in Mothers of Children with Autism - Musayaroh, Siti; Abadi, Reza Febri; Maslahah, Sayidatul; Karina, Rr. Farhana Rizqi (Angstrom Centre of Education, 2024)
Parents of children with autism, especially mothers, experience more parental stress compared to mothers of typical children. The aim of this research was to discuss the relationship between social support perceived to mothers of children with autism and parental stress levels, and to investigate the relationship between the characteristics of the mothers/their children and parental stress. Fifty mothers of children with autism in Banten Province completed the Social Support Index (SSI) and Parental Stress Scale (PSS) through a Google Form. The data was analyzed using Pearson Correlation and multiple regression analysis. Results show that the mothers had high social support (M = 61.72) and experienced lower stress in parenting their children (M = 39.56). Moreover, SSI has a significant negative correlation with PSS (r = -.519, p = .01), indicating that the higher social support accepted by mothers of children with autism, the lower level of parental stress they experienced. Surprisingly, mothers of children with autism who have siblings have lower parental stress than those of them without siblings.